1907
DOI: 10.1017/s0022172400033180
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of the Micrococcus catarrhalis in Normal and Catarrhal Noses and its Differentiation from other Gram-negative Cocci

Abstract: The Micrococcus catarrhalis was first isolated by Kirchner (1890) from cases of influenza-like illness. Since then several epidemics of acute catarrh and bronchitis associated with this organism have been recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1928
1928
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
0
5
0
1
Order By: Relevance
“…Dis., 10:89, 1991). This inverse relationship between age and colonization has been known since 1907 (9) and is still present today (81; C. Hol, C. M. Verduin, E. van Dijke, J. Verhoef, and H. van Dijk, Letter, Lancet 341:1281, 1993). At present, there is no good explanation for the difference in rates of colonization between children and adults; one explanation may be the age-dependent development of secretory immunoglobulin A (IgA).…”
Section: Carriagementioning
confidence: 88%
“…Dis., 10:89, 1991). This inverse relationship between age and colonization has been known since 1907 (9) and is still present today (81; C. Hol, C. M. Verduin, E. van Dijke, J. Verhoef, and H. van Dijk, Letter, Lancet 341:1281, 1993). At present, there is no good explanation for the difference in rates of colonization between children and adults; one explanation may be the age-dependent development of secretory immunoglobulin A (IgA).…”
Section: Carriagementioning
confidence: 88%
“…A corresponding age relationship was observed by Arkwright (9) in 1907. "Micrococcus catarrhalis" was isolated "from a much larger proportion of infants under one year than of older children or of adults: the last furnished proportionately the fewest strains" (9). Further evidence came from three studies in the 1980s of nasopharyngeal specimens taken in fall or winter months from Swedish children who showed no symptoms of respiratory infections.…”
Section: Analogy Between B Catarrhalis and N Meningitidismentioning
confidence: 99%
“…A current textbook (324) estimates its presence as 12% in the nose and nasopharynx and 10 to 97% in the oropharynx. Early studies had found "Micrococcus catarrhalis" in 33% of nasal cultures (9), 18% of nasopharyngeal cultures (112), and 46% of nose and throat cultures from healthy persons and 45% of subjects with the common cold (130). "M. catarrhalis" was recognized as a gram-negative diplococcus, capable of growth at 22°C, which displays certain well-described colony characteristics and has no action on "fermentable substances" (9,108,112).…”
mentioning
confidence: 99%
“…2 Modified Thayer Martin medium (MTM) containing vancomycin 3mg/l, colistin 75 mg/l, trimethoprim 5mg/l and nystatin 12500 U/i (Difco Laboratories). 3 MacConkey agar (Oxoid code No CM7). 4 Crystal violet blood agar, bi-layer plate: lower layer, columbia agar (Oxoid code CM331); upper layer, Columbia blood agar with crystal violet at final concentration 0 0002%.…”
Section: Culture Characteristicsmentioning
confidence: 99%